Documenting and characterising gestational weight gain beliefs and experiences among Marshallese pregnant women in Arkansas: a protocol for a longitudinal mixed-methods study - Pearl A McElfish; Britni L Ayers; Cari A Bogulski; Lauren Haggard-Duff; Aline Andres; Elisabet Børsheim (BMJ Open)
Introduction Arkansas has the largest population of Marshallese Pacific Islanders residing in the continental USA. The Marshallese have higher rates of obesity, type 2 diabetes, pre-term births, low birthweight babies, infant mortality, and inadequate or no prenatal care. Despite the high rates of cardiometabolic and maternal and child health disparities among Marshallese, there are no studies documenting gestational weight gain or perceptions about gestational weight gain among the Marshallese population residing in the USA.Methods and analysis This paper describes the protocol of a mixed-methods concurrent triangulation longitudinal study designed to understand gestational weight gain in Marshallese women. The mixed-methods design collects qualitative and quantitative data during simultaneous data collection events, at both first and third trimester, and then augments that data with postpartum data abstraction. Quantitative and qualitative data will be analysed separately and then synthesised during the interpretation phase.Ethics and dissemination The study used a community engaged approach approved by the University of Arkansas for Medical Sciences Institutional Review Board (#228023). The research team will disseminate results to study participants, research stakeholders (clinics, faith-based organisations and community-based organisation), the broader Marshallese community and fellow researchers. Results will be disseminated to study participants through a one-page summary that show the aggregated research results using plain language and infographics.